Stroke, Dementia and Atrial Fibrillation - Russo, Vincenzo; Proietti, Riccardo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The present special issue will lead you to discover the association between cerebrovascular events, cognitive impairment and atrial fibrillation, through update reviews and original articles exploring the pathophysiological mechanisms underpinning this association and describing the latest results in term of stroke prevention in AF. An interesting scientific journey that reflects the recent advances in pharmacological treatments and interventional procedures involving both mind and heart.